Skeletal posterior crossbite in patient with mandibular asymmetry: an alternative solution - ROMANO,Fábio Lourenço (2021)
ABSTRACT Introduction: Skeletal posterior crossbite (SPCB) has a multifactorial etiology, as it may be caused by parafunctional habits, atypical position of the tongue, tooth losses and maxillary or mandibular transverse skeletal asymmetries. Skeletal involvement may lead to facial changes and an unfavorable aesthetic appearance. The treatment of SPCB diagnosed in an adult patient should be correctly approached after the identification of its etiologic factor. Surgically-assisted rapid maxillary expansion (SARME), one of the techniques used to correct SPCB in skeletally mature individuals, is an efficient and stable procedure for the correction of transverse discrepancies that may be performed in the office or in a hospital. Objective: This study discusses the results of asymmetrical SARME used to correct unilateral SPCB associated with transverse mandibular asymmetry. Conclusion: The treatment alternative used in the reported case was quite effective. At the end of the treatment, the patient presented adequate occlusion and facial aesthetics.